2006
DOI: 10.1158/0008-5472.can-05-4488
|View full text |Cite
|
Sign up to set email alerts
|

The DNAN-Glycosylase MED1 Exhibits Preference for Halogenated Pyrimidines and Is Involved in the Cytotoxicity of 5-Iododeoxyuridine

Abstract: The base excision repair protein MED1 (also known as MBD4), an interactor with the mismatch repair protein MLH1, has a central role in the maintenance of genomic stability with dual functions in DNA damage response and repair. MED1 acts as a thymine and uracil DNA N-glycosylase on T:G and U:G mismatches that occur at cytosine-phosphate-guanine (CpG) methylation sites due to spontaneous deamination of 5-methylcytosine and cytosine, respectively. To elucidate the mechanisms that underlie sequence discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
53
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 52 publications
2
53
0
Order By: Relevance
“…5A and 8C), in agreement with results reported previously for hemimethylation immediately adjacent to the mismatch (52). Also, the enzymatic activity of the glycosylase domain of MBD4 itself has been shown, in some previous studies, to prefer T/G mismatches within the context of a CpG site when the site is hemimethylated (65). In the study by Turner and coworkers, the single-turnover rate of the enzyme was found to be 17% higher than that in the nonmethylated context (65).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…5A and 8C), in agreement with results reported previously for hemimethylation immediately adjacent to the mismatch (52). Also, the enzymatic activity of the glycosylase domain of MBD4 itself has been shown, in some previous studies, to prefer T/G mismatches within the context of a CpG site when the site is hemimethylated (65). In the study by Turner and coworkers, the single-turnover rate of the enzyme was found to be 17% higher than that in the nonmethylated context (65).…”
Section: Discussionsupporting
confidence: 90%
“…Surprisingly, the activity of the glycosylase is likewise unaffected by the presence of the methyl-binding domain (51). Despite the aforementioned preference of the enzyme for methylase recognition sites, there is some disagreement about whether the activity of the intact protein is affected by the presence or absence of a methyl group on the DNA strand opposite the mismatched T (52,65,66).…”
mentioning
confidence: 99%
“…MED1 acts as a thymine and uracil DNA N-glycosylase on T:G and U:G mismatches that occur at cytosine-phosphate-guanine (CpG) methylation sites due to the spontaneous deamination of 5-methylcytosine and cytosine, respectively. This event indicates that MED1 is involved in the removal of methylated DNA (12). Abnormal DNA methylation (including hypermethylation and hypomethylation) is a hallmark of the majority of cancers, including colon, lung, prostate and breast cancers, and contributes to carcinogenesis by silencing tumor suppressor genes, upregulating oncogenes and/or reducing genomic stability (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, MED1 removes Ts mispaired with those Gs that are methylated by these drugs ( 6 O-methyl-guanine), suggesting that MED1 may be involved in the resistance to these drugs. 10,11 In fact, Cortellino et al and Sansom et al demonstrated that a normal MED1 is required for apoptosis of cells damaged by the mutagenic effect of several other drugs, including methylating agents. 10,12 In MED1-deficient cells, the DNA damage accumulates without the induction of cell cycle arrest and apoptosis.…”
mentioning
confidence: 99%